The Prognostic Significance of Anemia in Patients With Heart Failure: A Meta-Analysis of Studies From the Last Decade - Xia, Haijiang; Shen, Hongfeng; Cha, Wei; Lu, Qiaoli (Frontiers in Cardiovascular Medicine, 2021)
Background: Anemia is a commonly occurring comorbidity in patients with heart failure (HF). Although there are few reports of a higher prevalence of mortality and hospitalization-related outcomes due to accompanying anemia, other studies suggest that anemia does not have an adverse impact on the prognostic outcomes of HF. Two meta-analyses in the past decade had reported the adverse impact of anemia on both mortality and hospitalization- related outcomes. However, only one of these studies had evaluated the outcome while using multivariable adjusted hazard ratios. Moreover, several studies since then reported the prognostic influence of anemia in HF. In this present study, we evaluate the prognostic impact of anemia on mortality and hospitalization outcomes in patients with HF. Methods: We carried out a systematic search of the academic literature in scientific databases EMBASE, CENTRAL, Scopus, PubMed, Cochrane, ISI Web of Science, and clinicaltrial.gov, and MEDLINE based on PRISMA guidelines. Meta-analysis was then performed to evaluate the effect (presented as risk ratio) of anemia on the overall mortality and hospitalization outcome in patients with HF. Results: Out of 1,397 studies, 11 eligible studies were included with a total of 53502 (20615F, 32887M) HF patients (mean age: 71.6 ± 8.3 years, Hemoglobin: 11.9 ± 1.5 g/dL). Among them, 19794 patients suffered from anemia (Hb: 10.5 ± 1.6), and 33708 patients did not have anemia (Hb: 13.2 ± 1.7 g/dL). A meta-analysis revealed a high-odds ratio (OR) for the overall mortality in patients with anemia (OR: 1.43, 95% CI: 1.29 to 1.84). A high-risk ratio was also reported for hospitalization as outcome in patients with anemia (1.22, 1.0 to 1.58). Conclusion: This systematic review and meta-analysis provide evidence of the high risk of mortality and hospitalization-related outcomes in patients with HF and anemia. The study confirms the findings of previously published meta-analyses suggesting anemia to be an important and independent risk factor delineating the prognostic outcome of chronic HF.